The Product Mix Analysis at Eilaji Coffee Sumedang - Wawan Gunawan; Nadia Mutmainah (SINTESA, 2022)
Stimulated by the development of middle-class society and the changes of people's lifestyle, the performance of the coffee industry in domestic area, especially in Sumedang, has significantly increased. Eilaji Coffee Sumedang is a coffee shop that located at Budi Asih street, number 2 (side to the Sumedang Prison). Because of that, to win the competition competitively, Eilaji Coffee Sumedang needs to develop and improve their products through the Product Mix. This study purposed to determine the Product Mix Analysis at Eilaji Coffee Sumedang. This study used the Qualitative Research Method, how to collect the data is by doing the observation, interview and documentation. The Products Mix contained at Eilaji Coffee Sumedang are the Width Level of Product Mix, the Length Level of Product Mix, the Depth Level of Product Mix and the Product Mix Consistency. Eilaji Coffee Sumedang consistently processed their various coffee drinks with the exclusive and unique taste in each their coffee products by using the product mix system in order to get the well-received by their consumers.